Kerosene draw at Petronas Terengganu Refinery - Abd. Manaf, Noor Hazilah; Hamdan, Mohd Hisham; Fadhil, Shahril Goh (International Islamic University Malaysia, 2011)

(untitled)
Six Sigma is a quality improvement methodology that is widely used by both service and manufacturing organisations. It was pioneered by Motorola but gained wide-reaching recognition through extensive adoption of the methodology by General Electric. Six Sigma focuses on the DMAIC principles of define, measure,analyse, improve, and control with team-based decision-making and problem-solving approach as the mainstay of its implementation. Kerosene draw at Petronas Terengganu Refinery was improved from 69.7 m3 /hr before implementation of Six Sigma to 73.03 m3 /hr after its successful implementation, which represented a breakthrough improvement from -1.47 to 12.32 sigma level. Headed by a Master Black Belt, the Six Sigma project team first began by mapping the process of kerosene draw in the define stage, followed by rigorous statistical analysis in analysing the critical to quality characteristics (CTQs)of the process, before arriving at an optimum process without compromising the quality of the kerosene. During the first six months of implementation, the project made a cost-savings of RM 5.5 million without any capital expenditure.